(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Jewellery has come a long way from the time ofmanufacturing during the days of Indus valley civilization to exportingproducts globally and has now become an integral part of India’s traditions andculture. With the advent of information technology and World Wide Web jewellersare now able to make their products available for a wider market and cater toall its potential customers. Still the customers are not very keen onpurchasing Jewellery online as they feel the need for touch and feel factor. E-commerce has become one of the major modifications tothe retail platform in this industry. In India, the Jewellery industry does abusiness of approximately 11000 crores or 215 million through e-commerce asprovided by Internet and Mobile Association of India (IAMAI). The purpose of this study to evaluate consumer perceptionof online shopping related to jewellery items. Respondents were selected fromdifferent genders, age groups and occupations having internet shoppingexperience research was conducted with the help of a structured questionnaire.